REMARKS ON LANGUAGE ACQUISITION AND LITERACY: LANGUAGE ACQUISITION AND TEACHING, FREE READING, "TEST-PREP" AND ITS CONSEQUENCES, THE USE OF THE FIRST LANGUAGE, WRITING, AND THE GREAT NATIVE SPEAKER TEACHER DEBATE - Stephen D. Krashen (Indonesian JELT, 2015)
This paper reviews the arguments for comprehensible input (the"comprehension hypothesis" and discusses some of itsapplications to beginning and intermediate language teaching,including free voluntary reading as a bridge from conversationalto academic language. The comprehension hypothesis providessome guidance on the proper use of the first language in secondlanguage teaching and helps explain what writing can andcannot do. Finally, the comprehension hypothesis contributes tothe Great Native Speaker Teacher debate: We want teachers (1)to understand language acquisition, (2) to understand languagepedagogy, and (3) to speak the language well. My point is thatnumber (3) alone is not enough, even if the teacher is a nativespeaker.Keywords: comprehensible input, language acquisition,TPR, Natural Approach, TPRS, shelteredsubject matter teaching, free voluntary reading,writing